Cognitive Collaborations: Bidirectional Functional Connectivity Between the Cerebellum and the Hippocampus - Yu, Wilson; Krook-Magnuson, Esther (Frontiers in Systems Neuroscience, 2015)
There is a growing recognition that the utility of the cerebellum is not limited to motor control. This review focuses on the particularly novel area of hippocampal-cerebellar interactions. Recent work has illustrated that the hippocampus and cerebellum are functionally connected in a bidirectional manner such that the cerebellum can influence hippocampal activity and vice versa. This functional connectivity has important implications for physiology, including spatial navigation and timing-dependent tasks, as well as pathophysiology, including seizures. Moving forward, an improved understanding of the critical biological underpinnings of these cognitive collaborations may improve interventions for neurological disorders such as epilepsy.